THE EFFECT OF VISUAL THINKING STRATEGY ON THE VOCABULARY MASTERY OF STUDENTS IN VOCATIONAL HIGH SCHOOL - Capital, Henry Regie Leo; Maskhur, Muhammad; Ettyani, Ettyani; Nursaputri, Esamada Rose; Sulistyaningsih, Sulistyaningsih (English Teaching Journal : A Journal of English Literature, Language and Education, 2023)
The objectives of this research is to find out whether the Visual Thinking Technique has a significant effect on students' vocabulary mastery. This study used a quantitative method and employed T-test to inquire any significance change of the participant score of vocabulary mastery. The second and third meetings are the treatments, the students are taught vocabulary using Visual Thinking Techniques in the experimental class, and the students are taught vocabulary with the lecturing method in the control class. In pre-test Data Normality Test Classes N p-value Experiment 10 0,677, Control 10 0,623. From the results of the normality test it is known that the p-value for pre-test data in the experimental class and control class is 0.677 and 0.623 respectively, this p-value is greater than the 0.05 significance level. Post-test Data Normality Test Classes N p-value Experiment 10 0,125 Control 10 0,423. From the results of the normality test it is known that the p-value for post-test data in the experimental class and control class is 0.125 and 0.423 respectively, this p-value is greater than the 0.05 significance level. This means that H0 is rejected or there is a significant difference in the average students' vocabulary mastery between students in the control class and the experimental class. Therefore, the visual thinking strategy has a significant effect on students' vocabulary mastery.